User generated content – users, community of users and firms: toward new sources of co-innovation?. Issue 6 (12th September 2016) - Simon, Jean Paul
Abstract : Purpose: The paper aims at dealing with the role of users in the creation (or curation) and distribution of digital contents. User generated contents (UGCs) refer to a variety of media such as Wikis, question-answer databases, digital video, blogging, podcasting, forums, review sites, social networking, social media and mobile phone photograph. It attempts assessing their potential role as co-innovators. The paper follows the progressive creation of a new space for users, tracking its specific forms in each subsector of the media and content industries. Each subsector reveals a disruption in the production and circulation of new content. Design/methodology/approach: The paper is based on desk research, a review of literature, review of the technical journals, and analysis of annual reports. The paper is part of an on-going research project on media and content industries. Findings: The paper argued that since 2007 (release of iPhone and Kindle) the landscape went through a dramatic change, scaling up. It illustrates how the entire value chain of content (production/distribution/consumption) has opened up. The amount of UGC produced triggered a qualitative jump, ushering in new modes of interaction between the customers and creators, without necessarily turning the consumer into a full-fledge producer. The UGC model adds another source of production, thereby increasing diversity, ushering in new ways for talent scouting. It reveals various forms of co-creation and the role of a community model while also showing its limits. Research limitations/implications: This paper concentrates on digital media and does not deal with any other aspect such as knowledge sharing (Wikis). The paper does not cover the reactions of traditional industry players to UGC (some elements are given for newspaper), neither possible policy and regulatory responses The paper relies mostly on reports from news agencies, consultancies or annual reports from companies so as to delineate the main trends. Practical implications: It shows that the role of customers did change within this context. The new channels offer novel ways to produce, curate and disseminate contents. It offers a range of examples from different industries. Social implications: The paper documents the participation of consumers in the production of content. it hints at the evolution of labour, alludes to the issue of diversity and of creativity, but does not address other societal issues. Originality/value: Some reports were devoted to UGC in 2007 (OECD) and 2008 (Idate-IVIR-TNO) but in spite of the major changes that took place over the past decade, the research has been scarce, or has concentrated on a specific segment of the media industry. The paper is trying to offer a comprehensive overview of the various segments. Each sub-segment of the media industry illustrates a specific dimension.